Almost Automorphic Solutions of Dynamic Equations on Time Scales - Lizama-Yanez, C (2013)
In the present work, we introduce the concept of almost automorphic functions on time scales and present the first results about their basic properties. Then, we study the nonautonomous dynamic equations on time scales given by x?(t)=A(t)x(t)+f(t) and x?(t)=A(t)x(t)+g(t, x(t)), t?T where T is a special case of time scales that we define in this article. We prove a result ensuring the existence of an almost automorphic solution for both equations, assuming that the associated homogeneous equation of this system admits an exponential dichotomy. Also, assuming that the function g satisfies the global Lipschitz type condition, we prove the existence and uniqueness of an almost automorphic solution of the nonlinear dynamic equation on time scales. Further, we present some applications of our results for some new almost automorphic time scales. Finally, we present some interesting models in which our main results can be applied. © 2013 Elsevier Inc.